2009
DOI: 10.1073/pnas.0812884106
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cell imaging of retinal ganglion cell apoptosis with a cell-penetrating, activatable peptide probe in an in vivo glaucoma model

Abstract: Molecular imaging probes have potential for in vivo identification of apoptosis and other intracellular processes. TcapQ, a cell-penetrating, near-infrared fluorescent peptide probe designed to be optically silent through intramolecular fluorescence quenching and activated by effector caspases, has been previously described and validated in vitro. Herein, using NMDA-induced apoptosis of retinal ganglion cells (RGCs), representing an in vivo rat model of glaucoma, we assessed the ability of TcapQ to image singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 45 publications
4
91
0
1
Order By: Relevance
“…A recent report now suggests that NMDA excitotoxicity of RGCs acts on Müller glia cells that then release TNF␣ that triggers RGC death via apoptosis (Lebrun-Julien et al, 2009). Other studies have also attributed NMDA-induced RGC death to apoptosis (Barnett et al, 2009;Goebel, 2009), while some laboratories have reported that in this model RGC death involves other mechanisms (Saggu et al 2010). Our results clearly show Otx2 and ZVAD, an anti-apoptotic drug, have similar and nonadditive effects in vitro and that, in the NMDA model of RGC excitotoxicity in vivo, Otx2 saves 100% of the cells and fully preserves visual acuity in the optomotor test.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A recent report now suggests that NMDA excitotoxicity of RGCs acts on Müller glia cells that then release TNF␣ that triggers RGC death via apoptosis (Lebrun-Julien et al, 2009). Other studies have also attributed NMDA-induced RGC death to apoptosis (Barnett et al, 2009;Goebel, 2009), while some laboratories have reported that in this model RGC death involves other mechanisms (Saggu et al 2010). Our results clearly show Otx2 and ZVAD, an anti-apoptotic drug, have similar and nonadditive effects in vitro and that, in the NMDA model of RGC excitotoxicity in vivo, Otx2 saves 100% of the cells and fully preserves visual acuity in the optomotor test.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have reported that intraocular NMDA injected leads to RGC loss through apoptosis and that RGC death can be partially protected with anti-apoptotic compounds Z-YVAD and Z-DEVD (Barnett et al, 2009;Lebrun-Julien et al, 2009). However, other studies have suggested that RGC death after NMDA also involves necrosis (Goebel, 2009;Saggu et al, 2010).…”
Section: Resultsmentioning
confidence: 84%
“…For example, a caspase-3-binding radiotracer, [ 18 F]ICMT-11, was recently used to study the induction of apoptosis by chemotherapeutic agents (67). Similarly, a cell-penetrating TcapQ was recently developed to improve the pharmacokinetic properties and improve delivery of FRET-based caspase probes (68). Additionally, nanoparticles have been used to detect caspase activity (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main models to induce RGC cell death in the retina is the injection of NMDA, which induces RGC apoptosis and necrosis through the secretion of TNF by Mueller Glia cells (Barnett et al, 2009;Lebrun-Julien et al, 2009). In a recent study, we demonstrated that Otx2 injected in the eye at nanomolar concentrations fully antagonizes RGC cell death induced by NMDA and preserves visual acuity (Torero Ibad et al, 2011) (Fig.…”
Section: Therapeutic Homeoproteinsmentioning
confidence: 99%